Seasonal composition, abundance and biomass of the subestuarine fish assemblage in Solís Chico (Río de la Plata estuary, Uruguay) - A. Acuña Plavan; R. Gurdek; N. Muñoz; J. M. Gutierrez; M. Spósito; P. Correa; A. Caride (Brazilian Journal of Biology)
Abstract The large estuaries can present long narrow branches called subestuaries or tidal creeks. These types of subsystems are distributed along the Uruguayan coast of the Río de la Plata estuary and are very important as nursery and refuge areas for fish. For the first time, the seasonal composition and abundance of the fish community of the Solís Chico subestuary was studied by using beach and gill nets. Fourteen species, mainly euryhaline (86%) presented a significant representation of juvenile stages. The fish community was dominated by Odontesthes argentinensis, Platanichthys platana, Mugil liza, Brevoortia aurea, Micropogonias furnieri and Paralichthys orbignyanus, similar to adjacent subestuaries. While Micropogonias furnieri and B. aurea were the most abundant species, some other species were rarely caught. A seasonal variation of the fish assemblage abundance was detected, with higher values in autumn showing a positive correlation with temperature. Species that complete their life cycle in the Río de la Plata estuary, some of which are relevant to fisheries (64% of the analyzed species) were captured in the Solís Chico subestuary. The importance of this environment as a transitional system for some estuarine fish species is advised.